First-Generation College Students' Persistence Intentions in Engineering Majors. (February 2017) - Garriott, Patton O.; Navarro, Rachel L.; Flores, Lisa Y.
This study examined the relationship between parental support, engineering-related (realistic/investigative themed) learning experiences, self-efficacy, outcome expectations, and persistence intentions in a sample of first-generation college student (FGCS) engineering majors ( N = 130). Parental support was assessed at the conclusion of an academic year and modeled as a predictor of other engineering-related variables assessed a year later using the social cognitive career theory framework. Results showed that parental support predicted realistic/investigative-themed verbal persuasion and vicarious learning, while realistic/investigative-themed performance accomplishments and physiological arousal predicted engineering self-efficacy. Realistic/investigative performance accomplishments also predicted outcome expectations. Self-efficacy and outcome expectations were predictors of engineering persistence intentions. Contrary to expectations, self-efficacy did not significantly predict outcome expectations. Mediation analyses revealed that the relationships of realistic/investigative-themed performance accomplishments and physiological arousal to persistence intentions were explained by self-efficacy. Results are discussed in terms of increasing retention of FGCS in engineering.